2017
DOI: 10.1302/2046-3758.63.bjr-2016-0207.r1
|View full text |Cite
|
Sign up to set email alerts
|

The revitalisation of flexor tendon allografts with bone marrow stromal cells and mechanical stimulation

Abstract: ObjectivesThe present study describes a novel technique for revitalising allogenic intrasynovial tendons by combining cell-based therapy and mechanical stimulation in an ex vivo canine model.MethodsSpecifically, canine flexor digitorum profundus tendons were used for this study and were divided into the following groups: (1) untreated, unprocessed normal tendon; (2) decellularised tendon; (3) bone marrow stromal cell (BMSC)-seeded tendon; and (4) BMSC-seeded and cyclically stretched tendon. Lateral slits were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…The confined environment created by the high natural polydispersity of Cr in the culture medium accelerates cleavage of the N‐ and C ‐ propeptides of the procollagen molecules by the N‐ and C ‐ proteinases, thereby creating the insoluble collagen molecule (40, 41). COL1A1 was not increased at 10% strain, which contradicts previous studies in which mechanical stimulation led to increased COL1A1 synthesis in TCs (82, 8789) and BMSCs (30, 90, 91), a process mediated by TGF‐β1 (92). Increased deposition of collagen types III, IV, V, and VI has been observed in fibroblasts (41), and increased deposition of collagen III has been described in BMSCs (47) and corneal fibroblasts (42) when using Cr as a crowder.…”
Section: Resultscontrasting
confidence: 89%
“…The confined environment created by the high natural polydispersity of Cr in the culture medium accelerates cleavage of the N‐ and C ‐ propeptides of the procollagen molecules by the N‐ and C ‐ proteinases, thereby creating the insoluble collagen molecule (40, 41). COL1A1 was not increased at 10% strain, which contradicts previous studies in which mechanical stimulation led to increased COL1A1 synthesis in TCs (82, 8789) and BMSCs (30, 90, 91), a process mediated by TGF‐β1 (92). Increased deposition of collagen types III, IV, V, and VI has been observed in fibroblasts (41), and increased deposition of collagen III has been described in BMSCs (47) and corneal fibroblasts (42) when using Cr as a crowder.…”
Section: Resultscontrasting
confidence: 89%
“…Second, we did not mechanically evaluate these samples in this study. Our prior study indicates that no significant difference in mechanical characteristics among normal tendon, LSDCT, and LSDCT + BMSCs was observed after 2 weeks of culture in vitro [19]. Also, the mechanical evaluation of tendon samples under ex vivo situation does not reflect the actual physiological condition after tendon or ligament reconstruction.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the volardorsal slits were shallow because of the oval shape of the flexor tendon cross-section. More recently, a lateral tendon slit technique was introduced to seed bone marrow stromal cells (BMSCs) to enhance the revitalization of DCT graft [19]. The result revealed that the seeded BMSCs (2 × 10 7 cells/mL) remained viable and would repopulate in the DCT graft after 2 weeks of culture.…”
Section: Introductionmentioning
confidence: 99%
“…). The cell density was chosen based on the previous reports . After cell seeding, the tendon was treated with cd‐SYN of the following formula: 46% native synovial fluid, 10% gelatin (Sigma), 1% 1‐ethyl‐3‐([3‐dimethylaminopropyl] carbodiimide hydrochloride) (Sigma), and 1% N‐hydroxysuccinimide (Sigma) in 0.1 M of 2‐[N‐morpholino] ethanesulfonic acid buffer (Sigma) (pH, 6.0).…”
Section: Methodsmentioning
confidence: 99%